Photosynthesis Performance and Antioxidative Enzymes Response of Melia azedarach and Ligustrum lucidum Plants Under Pb–Zn Mine Tailing Conditions - Huang, XinHao; Zhu, Fan; He, ZhiXiang; Chen, XiaoYong; Wang, GuangJun; Liu, MengShan; Xu, HongYang (Frontiers in Plant Science, 2020)
Lead-zinc (Pb-Zn) mine tailings pose a great risk to the natural environment and human health because of their highly toxicity. In this study, the responses of photosynthesis, chlorophyll fluorescenece and antioxidative enzyme of Melia azedarach and Ligustrum lucidum in the soil contaminated by Pb-Zn mine tailings were investigated. Results showed that Pb-Zn mine tailings significantly reduced net photosynthetic rates and leaf photosynthetic pigment content of both trees, and the reduction of net photosynthetic rates was mainly caused by their biochemical limitation (BL). The chlorophyll fluorescence parameters from Pb-Zn tailing stressed leaves indicated that Pb-Zn tailings affected PSII activity which was evident from the change values of energy fluxes per reaction center (RC): probability that an electron moves further than QA- (ETO/TRO), maximum quantum yield for primary photochemistry (TRO/ABS), the density of PSII RC per excited cross section (RC/CSO), the absorption of antenna chlorophylls per PSII RC (ABS/RC) and the turnover number of QA reduction events (N). Pb-Zn mine tailings also affected the oxidation and reduction of PSI, which resulted in a great increase of reactive oxygen species (ROS) contents and then stimulated the rate of lipid peroxidation. Moreover, both trees exhibited certain antioxidative defense mechanisms, as elevated superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) activities, then declined under high level of Pb-Zn tailing treatment. Comparatively, L. lucidum showed less extent effect on photosynthesis and higher antioxidative enzymes activities than M. azedarach, thus L. lucidum was more tolerance than M. azedarach at least under the described Pb-Zn tailing treatment.